Healthy Media Promotion, Knowledge Towards Clean and Healthy Life Behavior among Students - Pertiwi, Wiwik Eko; Kusuma, Andiko; Annissa, Annissa (Universitas Ahmad Dahlan, 2019)
Background: The clean and healthy life behavior (CHLB) needs to be implemented since the elementary school age where the main target is elementary school students. This is based on the problem that most diseases often occur in school-age children (ages 6-10 years) including diarrhea, acute respiratory infections, helminthiasis and other environmental-based and behavioral-based diseases. This study is aimed to determine the relationship between media exposure and knowledge with CHLB in elementary students. Method: This research was conducted in all elementary schools located in Kramatwatu Serang-Banten in the months of February-July of 2018, with the sample of the research being fifth-grade students with as many as 150 people taken by using the simple random sampling method. Result: The results showed that 68% of respondents had a good, clean and healthy life behavior. A total of 94.7% of respondents stated that they were exposed to clean and healthy life behavior by media information, and 68.7% of them had a good level of knowledge. The relationship test showed that there was no significant relationship between media exposure and knowledge with CHLB. Conclusion: The knowledge of elementary school students was good due to the teacher and health promotion media.